The Contribution of Education, Health, and Unemployment on HDI in East Java, Indonesia - Amrun Rosyid; Elok Damayanti; Sarmilah Sarmilah; ST Rohani; Syalwa Shabila (IJEBD (International Journal of Entrepreneurship and Business Development))
Purpose: This study aims to analyse the influence of education, health, and unemployment on the Human Development Index (HDI) in East Java, Indonesia. Given the disparities in HDI across regions, this research seeks to identify the extent to which these factors contribute to HDI variations in the province.